Evaluación del comportamiento agronómico con la utilización de bioestimuladores de crecimiento orgánico en dos variedades de amaranto (amaranthus spp) originarios de vniissok (rusia) para la producción de biomasa bajo cubierta, sector Lasso-Latacunga-Cotopaxi 2016”. - Casa Quinatoa, Cristina Rocío (2017)
In the present research the following was proposed: with the use of biostimulators of organic growth in two varieties of amaranth (Amaranthus spp) originating from VNIISSOK (Russia) for the production of biomass under cover. The experimental part of field was realized in the Farm Blooming Acres located in Lasso - Cotopaxi. The specific objectives of the research were to determine the best growth biostimulant for the biomass under cover, to determine the amaranth variety that is best suited under cover, to economically evaluate the best treatment. It was a Randomized Full Block Design with a 2x3 +1 factorial arrangement; Where A, are the varieties of amaranth, Nezhenka (Amaranthus hybridus L.), Valentina (Amaranthus tricolor L.), B were considered organic growth biostimulants (Basfoliar Algae, Seaweed Extrac, Basfoliar Aktiv) and 1 the control Biostimulants), with a total of 7 treatments that were arranged in three replicates, and during the whole vegetative period, the morphological parameters were evaluated every 15 days, obtaining as final results: emergency days, root length, stem length , Number of leaves and size of inflorescence. In the accumulation of biomass the best treatment was evidenced in T5 (Valentina, Seaweed Extrac) with 227.19gr and in T2 (Nezhenka, Seaweed Extrac) with 296.97gr. According to the economic analysis, the best treatment was T2 (Nezhenka, Seaweed Extrac) with an economic benefit of field of $ 13680 per hectare, while for the T5 (Valentina, Seaweed Extract) the profit was $ 18260. The results conclude that the action of the biostimulator Seaweed Extract and its influence on the biometric parameters evaluated is the most effective. It is recommended to use the Valentina variety (Amaranthus tricolor) to obtain by-products and the Nezhenka (Amaranthus Hybridus) variety for consumption as a vegetable.